2011
DOI: 10.1556/aagr.59.2011.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation: Enhanced cadmium (Cd) accumulation by organic manuring, EDTA and microbial inoculants (Azotobacter sp., Pseudomonas sp.) in Indian mustard (Brassica juncea L.)

Abstract: Phytoremediation is an approach designed to extract excessive heavy metals from contaminated soils through plant uptake. Cadmium (Cd) is among the elements most toxic to living organisms. Health hazards associated with the lethal intake of Cd include renal (kidney) damage, anaemia, hypertension and liver damage. A greenhouse experiment was carried out with Indian mustard (Brassica juncea) grown on artificially spiked soil (100 μg Cd g−1) with EDTA (2 mmol kg−1 in 5 split doses), FYM, vermicompost (VC) and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…It was found only in the pot experiment that the abundance of microorganisms is increasing with the plant age. The connection of microbial presence and activity with plantnecessity was already demonstrated among serious environmental stress conditions in several previous publications (Vivas et al, 2006;Panwar et al, 2011;Domonkos et al, 2013). Testing the MPN abundance of microorganisms in the tomato plant rhizosphere, differences among the used treatments were not found significantly in our study.…”
Section: Discussionmentioning
confidence: 70%
“…It was found only in the pot experiment that the abundance of microorganisms is increasing with the plant age. The connection of microbial presence and activity with plantnecessity was already demonstrated among serious environmental stress conditions in several previous publications (Vivas et al, 2006;Panwar et al, 2011;Domonkos et al, 2013). Testing the MPN abundance of microorganisms in the tomato plant rhizosphere, differences among the used treatments were not found significantly in our study.…”
Section: Discussionmentioning
confidence: 70%
“…FYM, Vermicompost and EDTA also increased the Cd uptake significantly with and without microbial inoculates in the shoots and roots. The results indicated that Vermicompost in combination with bioinoculants is a better solution for the phytoremediation of Cd by Indian mustard from Cd-contaminated soil, giving the highest uptake value in the shoot in the Cd VC+M treatment (2265.7 µg/pot), followed by Cd EDTA+M (2251.2 µg/pot), Cd FYM+M (1485.7 µg/pot) and Cd 100+M (993.1 µg/pot) (Panwar, 2010). Simon et al (2008) reported that crop species removed considerable amounts of cadmium from solution containing Cd after 48 hours of exposure.…”
Section: Microbial Biomass In Phytoremediationmentioning
confidence: 99%
“…Many studies have shown increased plant availability of various heavy metals following application of EDTA or other chelating agents such as N‐(hydroxyethyl)‐ethylenediaminetriacetic acid (HEDTA), nitrilotriacetic acid (NTA) or diethylenetriaminepentaacetic acid (DTPA) ( e.g ., Chen and Cutright , ; Hseu et al, ). As such, the phytoremediation potential of plants can be improved substantially by using chelating agents ( Blaylock et al, ; Vassil et al, ; Grčman et al, ; Piechalak et al, ; Epelde et al., ; Panwar et al, ). Many studies have focused on lead (Pb) in relation to phytoremediation and EDTA application, as it is one of the most important metallic soil contaminants ( Blaylock et al, ; Saifullah et al, ).…”
Section: Introductionmentioning
confidence: 99%